Voluntary financial and non-financial disclosure on zakat in the financial reports of Islamic banks in Malaysia - Salehah Zafirah bt Zulkepli (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
The objective of the study is to analyse the Islamic banks voluntary disclosure practices on zakat. The study examines the relationship between the extent of zakat disclosures and specific characteristics (i.e. amount of zakat, size of the bank, and profitability) of Islamic banks. The study used a zakat disclosure checklist based on AAOIFI FAS 9 and MASB TRi-1, which consist of 5 items of Disclosure Index (DI) and 5 items of Disclosure Length (DL) to measure the extent of zakat disclosure. The data were collected from the 2007 to 2011 of annual reports from the 17 Islamic banks in Malaysia. The main statistical tests conducted were descriptive statistics, correlation and regression analysis. From the findings, Affin Islamic Bank and Kuwait Finance House have sustained good zakat disclosure practices for both DI and DL. This might be due to these banks are among the long-established banks as compared to the others. Generally, the results show that there is still lack of reporting on zakat by the Islamic banks especially on non-financial disclosure in DL. The finding indicates that zakat financial disclosures seem to disclose more than zakat non-financial disclosures. This might be due to there is no specific standard that required them to disclose in detail on the information. Therefore the number of words counted would be less. The results revealed that a zakat amount has the highest correlation coefficient to the Disclosure Length. For the regression analysis, zakat amount has showed positive significant relationship to zakat disclosure. Thus, the hypothesis was accepted. However, total asset has showed positive relationship but not significant either for DI or DL. Thus, hypothesis 2 was rejected. Finally, return on equity has negative relationship to the extent of disclosure and not significant either for DI or DL. Therefore, hypothesis 3 was also rejected.